Impact of digital marketing capabilities on market performance of small to medium enterprise agro-processors in Harare, Zimbabwe - More Chinakidzwa; Maxwell Phiri (Verslas: Teorija ir praktika / Business: Theory and Practice, 2020)
The importance of marketing capabilities continues to grow yet research remains concentrated in developed markets. Although several researchers provide evidence of the influence of marketing capabilities on market performance, very little of similar evidence exists in the digital marketing domain. Empirical evidence of the impact of digital marketing capabilities on market performance of small to medium enterprise (SME) agro-processors particularly from developing countries remains scarce. The purpose of this paper was to investigate the impact of digital marketing capabilities on SME agro-processors' both intermediate and final market performance outcomes. To achieve this, we conducted a survey of 298 SME agro-processors' managers and owners in Harare, Zimbabwe. A mixed sampling approach consisting of quota and stratified sampling approaches was adopted. We distributed a closed-ended questionnaire through the drop-off & pick-up and interviewer-based methods. The data was analysed statistically using STATA version 15. Multiple logistic regression was conducted to determine impact of digital marketing capabilities on market performance. Our findings indicate that digital strategy development & execution, digital market innovation, e-market sensing and leadership capabilities positively influence intermediate market outcomes of customer awareness, customer attitudes, availability, and brand associations. However only digital strategy development & execution capability was positively associated with final market performance outcomes of sales growth, market share and profitability. These results imply that agro-processors must develop digital marketing capabilities that enable them to move beyond intermediate market outcomes to attain the primary business objectives of profitability, sales growth and market share. Attaining intermediate market outcomes only is not enough for business sustainability. The study contributes to literature by extending the marketing capabilities discussion to the digital marketing environment in a developing country context. This was important because marketing knowledge is contextual, as such cannot easily be transferred from one market to the other.
Keywords: M31; 650; digital marketing; capabilities; agro-processors; market performance; SMEs; Zimbabwe